Analisis Ability to Pay dan Willingness to Pay dalam Perencanaan Transportasi Rel di Ibukota Provinsi Aceh - I M Meilinda; , S M Maulida; R M Yusputri; A Rahmad; U A Pratama (Universitas Iskandar Muda, 2026)
The demand for transportation modes continues to increase year by year, in line with the growing population, which consequently raises the need for adequate transport services. Public transportation plays a crucial role in addressing this issue, with rail-based systems such as monorails being one viable solution. This has led to the emergence of a proposal to develop a monorail system in the capital region of Aceh Province. To ensure the smooth operation of this monorail, it is essential to analyze the financial boundaries of users in terms of their ability and willingness to pay. Therefore, this study aims to determine the extent of users’ financial capacity and willingness to pay for monorail fares. These values are assessed using the Ability to Pay (ATP) and Willingness to Pay (WTP) approaches. The sampling method applied is stratified random sampling, which considers population strata, combined with the Stated Preference (SP) technique. Respondents were selected from residents of Banda Raya, Kuta Alam, Ulee Kareng, and Meuraxa subdistricts. Data analysis was conducted through tabulation of primary and secondary data using Microsoft Excel software. Based on the research findings, the ATP values are as follows: Banda Raya Rp32,330.30; Kuta Alam Rp33,035.63; Ulee Kareng Rp30,960.79; and Meuraxa Rp32,911.14. Meanwhile, the WTP values are: Banda Raya Rp19,632.00; Kuta Alam Rp27,273.00; Ulee Kareng Rp19,875.00; and Meuraxa Rp23,857.00.